Enhancement of systemic and lung-localized CD4+ T-cell immune responses by truncation of NS1 protein of a seasonal live influenza vaccine strain - Polina I. Prokopenko; Ekaterina A. Stepanova; Victoria A. Matyushenko; Alexandra Ya. Rak; Anna K. Chistyakova; Arina D. Kostromitina; Tatyana S. Kotomina; Igor V. Kudryavtsev; Artem A. Rubinstein; Alexey S. Komlev; Larisa G. Rudenko; Irina N. Isakova-Sivak (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. There is a large variety of licensed influenza vaccines worldwide, but their common limitation is rather narrow specificity and inability to protect against antigenic-drift variants of influenza virus. Therefore, optimization of immunogenic and cross-protective properties of licensed influenza vaccines is an urgent priority of public health agenda. One such approach is to modulate the immunogenic properties of live attenuated influenza vaccine (LAIV) by truncating the open reading frame of influenza virus non-structural protein 1 (NS1). The main objective of this study is to evaluate the immunogenic properties of the H1N1 seasonal LAIV strain by truncation of the NS1 protein to 126 amino acides.